Pelestarian Secara In Vitro Melalui Metode Pertumbuhan Lambat Pada Beberapa Genotipe Ubi Jalar (Ipomea Batatas (L) Lam) - Jean K J Laisina (Agrologia, 2013)
The objectives of this research were to estimate responses of several sweet potato genotypes in preservation media through in vitro slow growth preservation, and to achieve cheap and accessible media. Experiment was arranged in a completely randomized design with a single factor. The experimental factor was sweet potato genotype (Sukuh, 421.34,343.15 and 2040.8). These genotype were tested in a preservation media which consisted of 15% coconut water +  30 mg/l aspirin + 50 g/l sucrose + 7 g/l agar. Experiment was replicated four times. Data was analyzed parametrically and non-parametrically. The result showed that genotype gave high responses to preservation media. Genotype Sukuh produced highest leaves while genotype 421.34 yielded highest numbers of root and internode. In the preservation medium of Genotype Sukuh through in vitro slow growth preservation, aspirin could be added to inhibit growth by increased leaf senesence. This experiment also showed that Hiponex (20:20:20) could be used as the basic media for in vitro preservation of sweet potato